Biopesticide enrichment in organic substrates for integrated management of Fusarium oxysporum f. sp. cepae and Meloidogyne incognita in onion - Priti, K; Rao, M S; Pavani, K V (Indian Journal of Plant Protection, 2020)
Field experiments were conducted to evaluate the effect of enriching biopesticides in organic substrates for the integrated pest management in onion. Biopesticide formulations of Bacillus pumilus and Pseudomonas spp. (P. monteilii, P. stutzeri, and P. entomophilia) were enriched in neem cake/vermicompost and evaluated for the efficacy under field conditions. Substrates were enriched at the rate of 1 kg talc formulation per 500 kg vermicompost or 200 kg neem cake; which was applied to the beds at the rate of 50 g/m2 as substrate treatment before transplantation. Results indicated that biopesticide-vermicompost or biopesticide-neem cake enriched substrate was more effective when compared with all other treatments. These treatments increased the plant growth and rhizospheric colonization of both biopesticides significantly and reduced the nematode infestation as well as disease incidence by Fusarium oxysporum f. sp. cepae. There was also a significant increase in the yield of the crop which was to the tune of 27.2%.